Protagonist Analysis of The Birthmark - M. Bintang Permata Anwar (UNIVED Press, 2020)
This thesis concerns the analysis of Protagonist Analysis of The Birthmark. The research question of this thesis was how the protagonist of the Birthmark short story by Nathaniel Hawthrone is. The design of the research was a descriptive design. A short story titled “The Birthmark,” written by Nathaniel Hawthorne in 1843. The plot centres around a prominent birthmark. Aylmer, the main character, is an intelligent, retired scientist whose passion of science is only rivaled by his love for Georgiana, his stunningly gorgeous new wife. Aylmer becomes preoccupied with a crimson, hand-shaped mark on his bride's left cheek shortly after the two marry, a mark Georgiana had deemed a